1996
DOI: 10.1073/pnas.93.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor mediates programmed cell death.

Abstract: The function of the recently discovered angiotensin II type 2 (AT2) receptor remains elusive. This receptor is expressed abundantly in fetus, but scantily in adult tissues except brain, adrenal medulla, and atretic ovary. In this study, we demonstrated that this receptor mediates programmed cell death (apoptosis). We observed this effect in PC12W cells (rat pheochromocytoma cell line) and R3T3 cells (mouse fibroblast cell line), which express abundant AT2 receptor but not AT1 receptor. The cellular mechanism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
378
1
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 658 publications
(412 citation statements)
references
References 22 publications
26
378
1
7
Order By: Relevance
“…[5][6][7][8] These agents effectively block the RAS by competitive antagonism of the action of angiotensin II at its cellular receptor site. 5,6,7,9 The AT 1 cellular receptor site appears to mediate most of the known actions of angiotensin II, although a second receptor site exists, AT 2 , 10 which appears to play an important role in apoptosis 11 and inhibition of cell growth and fibrillar collagen metabolism. 12 Valsartan is a new orally active angiotensin II antagonist which inhibits the RAS by selectively preventing the interaction of angiotensin II at its AT 1 cellular receptor site 9,13 Previous Phase I trials with valsartan have shown it to be well tolerated in single doses ranging from 10 to 400 mg once daily.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] These agents effectively block the RAS by competitive antagonism of the action of angiotensin II at its cellular receptor site. 5,6,7,9 The AT 1 cellular receptor site appears to mediate most of the known actions of angiotensin II, although a second receptor site exists, AT 2 , 10 which appears to play an important role in apoptosis 11 and inhibition of cell growth and fibrillar collagen metabolism. 12 Valsartan is a new orally active angiotensin II antagonist which inhibits the RAS by selectively preventing the interaction of angiotensin II at its AT 1 cellular receptor site 9,13 Previous Phase I trials with valsartan have shown it to be well tolerated in single doses ranging from 10 to 400 mg once daily.…”
Section: Introductionmentioning
confidence: 99%
“…79 Apoptosis in response to Ang II through the AT 2 receptor has been reported for R3T3 cells 79,96 and for rat ovarian granulosa cells as well. 97 In the latter cell type the AT 2 binding sites are increased under apoptotic conditions.…”
Section: At 2 Receptor and Signal Transductionmentioning
confidence: 95%
“…Additional evidence for a link of the AT 2 receptor and MAP kinase activity has been obtained from R3T3, PC12W and neuronal cells. 78,79 In these cell types, AT 2 receptor stimulation results in a decrease in MAP kinase activity. The antiproliferative character of the AT 2 receptor is reflected in the inhibition of MAP kinase activity.…”
Section: At 2 Receptor and Signal Transductionmentioning
confidence: 99%
“…As shown in our study, aortas of DOCA-salt rats, SHRs and angiotensin-infused rats exhibit apoptosis [23] . Numerous inflammatory modulators are also present in the vasculature, including reactive oxygen species [24] , NO [25] , angiotensin type 2 receptors [26] and the endothelin system [27] . The present study suggests that kallikrein/kinin regulates apoptosis in the aorta through countervailing influences on anti-apoptotic and pro-apoptotic systems.…”
Section: Discussionmentioning
confidence: 99%